2022
DOI: 10.1063/5.0082459
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical proton insertion modulates the hydrogen evolution reaction on tungsten oxides

Abstract: The development of new electrocatalysts for the hydrogen evolution reaction (HER) could reduce the dependence on Pt and other rare metals and enable large-scale production of hydrogen with near-zero carbon emissions. Mechanistic insight into the electrocatalytic activity of a material helps to accelerate the development of new electrocatalysts. Alternative electrocatalyst materials such as transition metal oxides and sulfides can undergo insertion reactions that change their properties. Recent reports indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 26 publications
1
22
0
Order By: Relevance
“…[ 27 ] More recently, the Augustyn and Mpourmpakis/McKone groups have both suggested that protons inserted into WO 3 govern the reactivity toward the hydrogen evolution reaction. [ 28,29 ] All these elements reinforce the idea that there is a crucial need to elucidate the key factors governing PICET reactions, and more specifically in aqueous unbuffered media. This is of prime interest for the development/optimization of not only water‐based electrochemical charge storage devices, but also of many water‐based energy conversion systems.…”
Section: Introductionmentioning
confidence: 67%
“…[ 27 ] More recently, the Augustyn and Mpourmpakis/McKone groups have both suggested that protons inserted into WO 3 govern the reactivity toward the hydrogen evolution reaction. [ 28,29 ] All these elements reinforce the idea that there is a crucial need to elucidate the key factors governing PICET reactions, and more specifically in aqueous unbuffered media. This is of prime interest for the development/optimization of not only water‐based electrochemical charge storage devices, but also of many water‐based energy conversion systems.…”
Section: Introductionmentioning
confidence: 67%
“…Protons have a smaller mass and volume as compared to other cations (H + mass ∼ 1.67 × 10 –15 ng, ionic radius ∼ 10 –5 Å; H 3 O + ionic size = 2.82 Å) and can also undergo hydrogen bonding . Reports show that protons are the predominant insertion species in mildly acidic electrolytes, necessitating the re-evaluation of cation insertion from aqueous electrolytes into TMOs. , Previous work by our group, as well as Miu et al, showed that PCET processes on TMOs can be coupled to HER, whereby proton insertion into tungsten oxides influences their HER activity. , Another report showed the importance of PCET reactions for facilitating high-energy oxidation reactions in multimetallic catalysts by circumventing the high-energy intermediates that form through stepwise reactions . Here, we aim to understand the role of electrolyte on PCET mechanisms in an important class of TMOs for aqueous energy applicationsthe titanium oxides.…”
Section: Introductionmentioning
confidence: 90%
“…8,9 Previous work by our group, as well as Miu et al, showed that PCET processes on TMOs can be coupled to HER, whereby proton insertion into tungsten oxides influences their HER activity. 10,11 Another report showed the importance of PCET reactions for facilitating high-energy oxidation reactions in multimetallic catalysts by circumventing the high-energy intermediates that form through stepwise reactions. 12 Here, we aim to understand the role of electrolyte on PCET mechanisms in an important class of TMOs for aqueous energy applications�the titanium oxides.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, we aim to answer whether a heterostructured microstructure forms, where in an ideal case, 2D The reaction mechanism of alkylamines with molybdic acids can be likened to that in isostructural tungstic acids, which has been described in literature to occur via a dissolution-reorganization mechanism that leads to a change in the morphology and particle size. 28,29 Scanning electron micrographs of MoO 3 -$2H 2 O and MoO x -OA (Fig. 1B and C) show an increased particle size aer reaction with octylamine.…”
Section: Structural Characterizationmentioning
confidence: 98%